Estudo da resposta da areia de Coimbra sob carregamento uniaxial - Fonseca, Mariana Pereira da (2018)
Submitted by Elsa Lemos (elsa@isec.pt) on 2018-04-09T16:03:52Z No. of bitstreams: 1 Mariana-Pereira-Fonseca.pdf: 10029702 bytes, checksum: 810428975ccc73adb867f86c87367ef7 (MD5)